2006
DOI: 10.1007/s00595-006-3331-5
|View full text |Cite
|
Sign up to set email alerts
|

Needle Track Dissemination of Follicular Thyroid Carcinoma Following Fine-Needle Aspiration Biopsy: Report of a Case

Abstract: Few reports have been concerned with the risk of needle track dissemination of tumor cells following fine-needle aspiration biopsy, especially for follicular thyroid nodules. A 61-year-old woman who underwent fine-needle aspiration biopsy and surgery 5 years previously for follicular thyroid adenoma presented with nodules that had developed in the sternocleidomastoid and omohyoid muscles of the anterior neck. These nodules were located along a line from the skin to the thyroid that coincided with the needle tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Another paper by Bravo et al (35) reported the establishment of primary cultures by needle aspiration biopsy in only one patient. However, the reports of cutaneous needle track seeding after fine needle aspiration biopsy (FNB) in patients with thyroid cancer have been published (36,37). FNA cytology overcomes this problem; in fact, in our Figure 4 The results of cell counting (2 h from the start of tetrazolium reaction) (meanGS.E.M.…”
Section: Discussionmentioning
confidence: 91%
“…Another paper by Bravo et al (35) reported the establishment of primary cultures by needle aspiration biopsy in only one patient. However, the reports of cutaneous needle track seeding after fine needle aspiration biopsy (FNB) in patients with thyroid cancer have been published (36,37). FNA cytology overcomes this problem; in fact, in our Figure 4 The results of cell counting (2 h from the start of tetrazolium reaction) (meanGS.E.M.…”
Section: Discussionmentioning
confidence: 91%
“…Its occurrence is an unavoidable complication. The present cases of needle track seeding of thyroid carcinoma suggested that it was important to give careful consideration to the indications for FNA [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In cases with a short interval between FNB and implantation, high cellular proliferative activity has been reported 21 . It seems that tumour size and aggressiveness increase the risk of needle track seeding 21,42 . Moreover, the implanted tumour may be more aggressive than the primary one 21,63 …”
Section: Needle Track Seeding (Tumour Implantation)mentioning
confidence: 99%